Complete Mitochondrial Genome of Suwallia teleckojensis (Plecoptera: Chloroperlidae) and Implications for the Higher Phylogeny of Stoneflies - Wang, Ying (Int J Mol Sci, 2018)
Stoneflies comprise an ancient group of insects, but the phylogenetic position of Plecoptera and phylogenetic relations within Plecoptera have long been controversial, and more molecular data is required to reconstruct precise phylogeny. Herein, we present the complete mitogenome of a stonefly, Suwallia teleckojensis, which is 16146 bp in length and consists of 13 protein-coding genes (PCGs), 2 ribosomal RNAs (rRNAs), 22 transfer RNAs (tRNAs) and a control region (CR). Most PCGs initiate with the standard start codon ATN. However, ND5 and ND1 started with GTG and TTG. Typical termination codons TAA and TAG were found in eleven PCGs, and the remaining two PCGs (COII and ND5) have incomplete termination codons. All transfer RNA genes (tRNAs) have the classic cloverleaf secondary structures, with the exception of tRNA(Ser(AGN)), which lacks the dihydrouridine (DHU) arm. Secondary structures of the two ribosomal RNAs were shown referring to previous models. A large tandem repeat region, two potential stem-loop (SL) structures, Poly N structure (2 poly-A, 1 poly-T and 1 poly-C), and four conserved sequence blocks (CSBs) were detected in the control region. Finally, both maximum likelihood (ML) and Bayesian inference (BI) analyses suggested that the Capniidae was monophyletic, and the other five stonefly families form a monophyletic group. In this study, S. teleckojensis was closely related to Sweltsa longistyla, and Chloroperlidae and Perlidae were herein supported to be a sister group.